2018
DOI: 10.1007/s10646-018-1988-3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant responses of Triticum aestivum plants to petroleum-derived substances

Abstract: Winter common wheat (Triticum aestivum L.) plants were cultivated on petroleum products contaminated soils with and without using biopreparation ZB-01. We determined the impact of soil contamination with petrol, diesel fuel and engine oil on selected antioxidant enzymes and the levels of antioxidants in the leaves of winter wheat. The impact of petroleum products on selected morphological characteristics of the plants, levels of nutrients and heavy metals was also assessed. Winter wheat was relatively resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 68 publications
6
40
1
Order By: Relevance
“…Both the oils (EO and DF) and P led to a more than a twofold decrease of the activity of CAT. Similar regularities in the application of oils were noted in the study by Rusin et al [14], where the test plant was winter wheat and the measurements were obtained four years after the instance of soil contamination. Tabassum et al [48] showed an almost threefold decrease in the activity of CAT in the aboveground parts of Mirabilis jalapa under the effect of used engine oil at a 2% concentration, which also corresponds to our results.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Both the oils (EO and DF) and P led to a more than a twofold decrease of the activity of CAT. Similar regularities in the application of oils were noted in the study by Rusin et al [14], where the test plant was winter wheat and the measurements were obtained four years after the instance of soil contamination. Tabassum et al [48] showed an almost threefold decrease in the activity of CAT in the aboveground parts of Mirabilis jalapa under the effect of used engine oil at a 2% concentration, which also corresponds to our results.…”
Section: Discussionsupporting
confidence: 79%
“…Marti et al [15] noted the lover activity of POD in the leaves of alfalfa growing on the soil contaminated by sediments from a refinery containing major quantities of hydrocarbons. However, Rusin et al [14], in their experiments on winter wheat, noted reversed relationships, i.e., the increase of the POD activity by nearly 20% under the effect of DF and P, and the decrease by 20% in the case of EO. The obtained discrepancies are indicative of the fact that the activities of antioxidative enzymes in plants depend on many factors, such as plant species, tissues analysed, and the conditions of the experiments, for example, pollutant concentration, and the type of pollutant [15,[52][53][54].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations